What Makes Tourists Stay in Homestay? The Correlation Between Service and Occupancy at Homestay Around Borobudur Super-Priority Destination - Rahayu, Emik; Asshofi, Izza Ulumuddin Ahmad; Pamungkas, Imang Dapit; Widyatmoko, Karis; Hapsari, Dian Indriana; Mulyono, Ibnu Utomo Wahyu; Nurjanah, Nurjanah; Irawan, Joseph Aldo; Pramitasari, Ratih; Ramdhani, Aji Kusumah (International Journal of Tourism and Hospitality in Asia Pasific, 2023)
Homestays are an alternative form of community-based accommodation that allows tourists to experience local wisdom in the community. Homestays in Borobudur Superprioritas-Tourist-Destinations should provide a comfortable accommodation option for tourists. However, they have not been managed optimally yet since limitation resources. This study aims to determine the service factors related to homestay occupancy.This research was part of the need assessment of homestay improvement programs. This study was observational-quantitative with a cross-sectional design. The respondents were twenty-two owners and managers of homestays in Candirejo Borobudur Village. Data were collected by self-administered questionnaire and analyzed by fisher-exact-testThe results showed that the quality of service related to occupancy. The service items associated with occupancy were booking procedures, payment notes, and rate information. Furthermore, factors associated with excellent service were older age and participation in homestay management training.